Bridging the gulf between academia and practice. (26th April 2014) - Pirie, Scott; Argyle, David; Corcoran, Brendan; Mellanby, Richard; Handel, Ian
Abstract : Edinburgh vet school recently launched PALS – a Practice and Academia‐Linked Study network – to strengthen links between academics and practitioners. Scott Pirie, David Argyle, Brendan Corcoran, Richard Mellanby and Ian Handel explain how vets and animals should benefit